MODEL REGRESI BINOMIAL NEGATIF TERBOBOTI GEOGRAFIS UNTUK DATA KEMATIAN BAYI - Afri, Lusi Eka (Edu Research, 2013)
Negative binomial regression model is used to overcome the overdispersion in Poisson regression model. This model can be used to model therelationship of the infant mortality and the factors incidence. Geographical conditions, socio cultural and economic differ one of location another locationcauses the factors that influence infant mortality is different locally. Geographically Weighted Negative Binomial Regression (GWNBR) is one ofmethods for modeling that count data have spatial heterogeneity and overdispersion.